CaPaS: an optimal security-aware cache replacement algorithm for cluster storage systems. (21st February 2012) - Nijim, Mais; Qin, Xiao; Yilmaz, Muhittin
In this paper, we introduce a novel dynamic cache management approach, i.e., a cache partitioning system (CaPaS), to optimise security levels in contemporary cluster storage systems for data-intensive applications with acceptable disk response times. CaPaS utilises an adaptive security control mechanism to adjust for varying workload conditions initiated by client-issued disk requests as well as security requirements and contains a cache partitioning scheme, a response-time estimator, and an adaptive security quality controller. The CaPaS algorithm solves a non-linear optimisation problem to increase the quality of security of disk requests in cluster storage systems while ensuring the disk requests to be completed within their desired response times. The efficiency of the proposed algorithm has been tested with the newly defined performance indicators on a cluster storage system including CaPaS, eight cryptographic and seven integrity services. Numerical simulation results demonstrate that the CaPaS algorithm improves the overall system performance enormously over two traditional baseline cache management algorithms.